Dampak Media Sosial terhadap Kesehatan Mental Remaja: Analisis Temuan Terbaru tentang Kecemasan, Depresi, dan FOMO - Hasibuan, Marsal Yunas Muliadi; Sabarrudin, Sabarrudin (YASIN, 2025)
The increasing use of social media among adolescents has had a significant impact on mental health, including symptoms of anxiety, depression, and Fear of Missing Out (FOMO). This phenomenon indicates that social media functions not only as a tool for communication and self-expression but also as a risk factor for adolescents’ psychological well-being. This study aims to analyze and synthesize recent findings on the relationship between social media use and adolescent mental health, as well as to identify intervention strategies through guidance and counseling approaches. A library research method was employed by reviewing primary sources such as academic journals and scholarly books, along with relevant secondary literature. The findings reveal that excessive use of social media is correlated with increased anxiety, depression, low self-esteem, and FOMO. Key contributing factors include cyberbullying, social comparison, and the pressure to construct a perfect online persona. Guidance and counseling interventions can address these issues through preventive, curative, and developmental services, focusing on enhancing digital literacy, emotional regulation, and psychological resilience. This study underscores the critical role of guidance and counseling in helping adolescents achieve balance between their online and offline lives, thereby supporting more stable and adaptive mental health.